Correlation betwen Fiber Intake and Energy Adequacy Based on 7-Days food diary of primary school children age 8-12 years in Surakarta - Ufairoh Maliha Shofwah; Afrianus Karo; Ari Murti Nindiyanti; Dian Nazikha Khusna; Niki Dwi Astuti; Setyaningrum Rahmawaty (Jurnal Dunia Gizi, 2020)
Background; The dietary fiber intake is an important part of childern’s diet and has a role in development of non-commuicable disease. The percentage of fiber intake based on the consumption of fruit and vegetables has been reported lack of children in Surakarta. Purposes; The aim of this research were to analyse the correlation between fiber intake and energy adequacy and to assess the contribution of food source containing fiber to energy intake of primary school children age 8-12 years old in Surakarta. Method; This type of this research was observational with a cross sectional approaches. One hundred and thirteen elementary school children age 8-12 years old in Surakarta were participated in this study which were recruited using multistage random sampling. The intakes data were analysed used Nutrisurvey fo Windows 2007 based on 7-days food diary filled by each child under her/his parent supervision. Dietary Allowance Intake for Indonesia called AKG 2013 was used as a refernce intake. Correlation test used Chi-Square. Result; Median fiber intake and energy adequacy of all children were 3.11 gram/day and 42% respectively.  There was no correlation between fiber and energy adequacy intake (p=0.05). Food source contributed fiber intake were white rice, processed flur products, and other vegetable food such as carrots, guava, and fermented soybean or tempeh. Conclusion; The low fiber intake in school age 8-12 years old in Surakarta was not correlated with their low energy adequacy.